Travel Clinic and Indonesian Hospital Code of Ethics - Made Indra Wijaya; I Made Aditya Mantara Putra; Luh Gede Pradnyawati (Community Service Journal of Law, 2023)
In 2022, COVID-19 cases are still reported occurring in Bali, however, the number of cases as well as its severity are no longer concerning as in 2020 and 2021. Bali has been reopened for both domestic as well as international tourists. Tourism begins to rise up and consequently, it brings about economics recovery. Various events, which are commonly abbreviated as MICE (meeting, incentive, conference, and exhibition), were and are planned to be hold in Bali. They continue taking place until they reach their peak during G20 Summit. Ubud, as one of tourist destinations in Bali, also rises up. The purpose of this community service program is to prepare Sanjiwani General Hospital to establish travel clinic through empowerment of its employees tailored to their backgrounds. The partner in this program is employee group who is broadly categorized into clinical and non-clinical groups. Clinical group consists of general practitioners, nurses, and pharmacists. Non-clinical group consists of administration staff and marketing staff. We initiated the program by conducting grand round, document assessment, and interview with several employees to get a glimpse of current situation so that we could provide training and education based on our findings. The situational analysis revealed that employees had not implemented travel medicine practice in accordance with international standard. Moreover, employees had not exposed with hospital code of ethics issues by Indonesian Hospital Association. We proceeded with workshop regarding travel medicine referring to the body of knowledge introduced by The National Travel Health Network and Centre (NaTHNaC) for clinical group and hospital ethical codes referring to hospital ethical codes introduced by The Indonesian Hospital Association for non-clinical group.